Legal responsibility for the ecological offences - Корнєєв, Юрій Валентинович; Садовський, Маркіян Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the article basic and special features of legal responsibility for the commitment of ecological offences, the necessity of creation of separate legal institute of ecologically-legal liability and its distinction from other types of responsibility are examined. To the most effective legal facilities, strengthening the ecological law and order belong measures of legal responsibility, that are used to the persons guilty in violation of ecolaw. As M. Dukhno marks, among other measures the legal types of responsibility have the greatest level of motivation of subjects of public relations on the following a way determined by a law. They appear to be for them as a "legal locomotive", that argues with a "reactive force" of the economic interest and also incentively rightobliged to follow an indicated direction. Now both researchers and practitioners pay a lot of attention to the issue of eco-liability. In fact all the textbooks on environmental law contain a relevant chapter. Among them it is appropriate to point out the works of V. Andreytseva, A. Bobylyeva, S. Gavrisha, V. Ivakin, S. Kravchenko, V. Munteanu, N. Titova, Y. Shemshuchenko and others. Thus, on the basis of foregoing it is possible to come to the conclusion, that there is a need to consider ecologically-legal responsibility as a separate complex legal institute. It is conditioned to those: - the significant feature of this type of legal responsibility is that it is used for the commitment of ecological offence; - legal responsibility is one of the forms of state compulsion, that is why is used or by the state, or in certain cases by the organs of local government, or administration of enterprises, organizations.